PEMBELAJARAN PERKUSI PADA EKSRAKURIKULER MARCHING BAND DI MAN 1 MEDAN - MUHAMMAD RIZKI HABIBI (Grenek: Jurnal Seni Musik, 2017)
In Extracurricular Learning Percussion Marching Band in MAN 1Medan. Faculty of Language and Arts University of Medan in 2015.This study aims to determine the learning percussion in extracurricularMarching Band in MAN 1 Medan, Iskandar Wlliam road no. 7BMedan. The experiment was conducted in February and March 2015.The method used in this research is descriptive qualitative method.Samples in this study are all members of the percussion players andcoaches totaled 14 people, amounting to one person percussion. Datacollection was conducted by literature study and field observations areinterviews and documentation. Once all the data collected, the data isanalyzed to answer all questions researchers. Analysis of the datapresented in the form of descriptive gradually in writing, thenclassified according to content or material concerned shall. After theanalysis conducted found that the learning outcomes percussionapplied by coaches in extracurricular Marching Band MAN 1 Theterrain is very nice and helpful for students. The students can readmusic well, signs of musical expression, know tempo. Courage anddiscipline of the students are also well embedded, so that the targetwhich is expected by the coach and the school can achieve its fullpotential.